Dopamine D2-receptor neurons in nucleus accumbens regulate sevoflurane anesthesia in mice - Niu, Li; Hao, Mengnan; Wang, Yanhong; Wu, Kai; Yuan, Chengdong; Zhang, Yu; Zhang, Jie; Liang, Xiaoli; Zhang, Yi (Frontiers in Molecular Neuroscience, 2023)
Introduction The mechanism of general anesthesia remains elusive. In recent years, numerous investigations have indicated that its mode of action is closely associated with the sleep-wake pathway. As a result, this study aimed to explore the involvement of dopamine D2 receptor (D2R) expressing neurons located in the nucleus accumbens (NAc), a critical nucleus governing sleep-wake regulation, in sevoflurane anesthesia. Methods This exploration was carried out using calcium fiber photometry and optogenetics technology, while utilizing cortical electroencephalogram (EEG), loss of righting reflex (LORR), and recovery of righting reflex (RORR) as experimental indicators. Results The findings from calcium fiber photometry revealed a decrease in the activity of NAcD2R neurons during the induction phase of sevoflurane anesthesia, with subsequent recovery observed during the anesthesia’s emergence phase. Moreover, the activation of NAcD2R neurons through optogenetics technology led to a reduction in the anesthesia induction process and an extension of the arousal process in mice. Conversely, the inhibition of these neurons resulted in the opposite effect. Furthermore, the activation of NAcD2R neurons projecting into the ventral pallidum (VP) via optogenetics demonstrated a shortened induction time for mice under sevoflurane anesthesia. Discussion In conclusion, our research outcomes suggest that NAcD2R neurons play a promotive role in the sevoflurane general anesthesia process in mice, and their activation can reduce the induction time of anesthesia via the ventral pallidum (VP).